Low-firing and microwave dielectric properties of BiNbO4 doped by CuO and V2O5 - Kim, IT; Kim, YH (GAUTHIER-VILLARS, 1996)
Effects of CuO and V2O5 addition on the sintering and microwave dielectric properties of BiNbO4 were investigated using a scanning electron microscopy, energy-dispersive spectroscopy, and network analyzer. Three batch compositions with different doping level, which were 0.05, 0.1, and 0.15 wt%, were prepared. It was observed that addition of CuO and V2O5 more than 0.1 wt% enabled low-firing of BiNbO4. Samples were fully sintered at 850 degrees C for 2 h. It was suggested that the addition of CuO and V2O5 enabled low-firing by forming liquid phase at low temperature. Permittivities of samples were insensitive to doping level whereas temperature coefficient of resonant frequency and quality factor showed much variation with doping level. More stable and linear temperature coefficient was obtained with increasing doping level whereas duality factor was decreased with increasing doping level.